Efficacy and safety of FLOT regimen vs DCF, FOLFOX, and ECF regimens as perioperative chemotherapy treatments for resectable gastric cancer patients; a report from the middle east - Pegah Farrokhi; Alireza Sadeghi; Mehran Sharifi; Rachel Riechelmann; Azadeh Moghaddas (Research in Pharmaceutical Sciences, 2022)
Background and purpose: This study aimed to compare the efficacy and toxicity of perioperative chemotherapy regimens including epirubicin, cisplatin, 5-fluorouracil (ECF), docetaxel, cisplatin, 5-fluorouracil (DCF), leucovorin, 5-fluorouracil, oxaliplatin (FOLFOX), and 5-fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) to identify the most effective chemotherapy regimen with less toxicity. Experimental approach: This retrospective cohort study (2014-2021) was based on 152 eligible resectable gastric cancer patients who had received one of the perioperative mentioned chemotherapy regimens and followed for at least two years. The primary endpoint of this study was overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and R0 resection. Findings / Results: Of included patients, 21%, 33.7%, 24.3%, and 21% had received ECF, DCF, FOLFOX and FLOT, respectively. After the median 30-month follow-ups, OS was higher with the FLOT regimen in comparison with other regimens (hazard ratio = 0. 276). The median OS of the FLOT regimen was 39 months. Besides, the median OS was 28, 25, and 21 months for DCF, FOLOFX, and ECF regimens, respectively. Moreover, a median PFS of 24, 18, 17, and 14 months was observed for FLOT, DCF, FOLFOX, and ECF regimens, respectively (Log-rank < 0.001). FLOT regimen showed 84. 4% ORR which was notably higher than other groups. Conclusions and implications: For resectable gastric cancer patients, the perioperative FLOT regimen led to a significant improvement in patients’ OS and PFS versus ECF, DCF, and FOLFOX regimens. As such, the FLOT regimen could be considered the optimal option for managing resectable gastric cancer patients.